Exosomes from Human Gingiva-Derived Mesenchymal Stem Cells Combined with Biodegradable Chitin Conduits Promote Rat Sciatic Nerve Regeneration - Rao, Feng (Stem Cells Int, 2019)
At present, repair methods for peripheral nerve injury often fail to get satisfactory result. Although various strategies have been adopted to investigate the microenvironment after peripheral nerve injury, the underlying molecular mechanisms of neurite outgrowth remain unclear. In this study, we evaluate the effects of exosomes from gingival mesenchymal stem cells (GMSCs) combined with biodegradable chitin conduits on peripheral nerve regeneration. GMSCs were isolated from human gingival tissue and characterized by surface antigen analysis and in vitro multipotent differentiation. The cell supernatant was collected to isolate the exosomes. The exosomes were characterized by transmission electron microscopy, Western blot, and size distribution analysis. The effects of exosomes on peripheral nerve regeneration in vitro were evaluated by coculture with Schwann cells and DRGs. The chitin conduit was prepared and combined with the exosomes to repair rat sciatic nerve defect. Histology, electrophysiology, and gait analysis were used to test the effects of exosomes on sciatic nerve function recovery in vivo. We have successfully cultured GMSCs and isolated exosomes. The exosomes from GMSCs could significantly promote Schwann cell proliferation and DRG axon growth. The in vivo studies showed that chitin conduit combined with exosomes from GMSCs could significantly increase the number and diameter of nerve fibers and promote myelin formation. In addition, muscle function, nerve conduction function, and motor function were also obviously recovered. In summary, this study suggests that GMSC-derived exosomes combined with biodegradable chitin conduits are a useful and novel therapeutic intervention in peripheral nerve repair.